A música na Educação Infantil: uma análise das práticas pedagógicas na Unidade de Educação Básica Maria José Serrão na cidade de São Luís – MA. - MATOS, Anna Karinne de Castro Neves (2024)
This research aimed to investigate how music has been treated in the educational actions of Early Childhood Education present at the Maria José Serrão Basic Education Unit in the city of São Luís, State of Maranhão, a public school in the Municipal Education Network. It was adopted the notion that pedagogical practice is a teaching action, carried out in an educational environment that has the intentionality of educating, guided by methodologies that are consistent with the pedagogical objective (Eleven, 2020). Sought to describe the musical activities developed by educators in this environment, as well as their training (initial and continued) in music, identifying the resources available in the school for carrying out musical activities. Alongside educators, we paid attention to their needs to develop musical education in early childhood education. The theoretical- methodological approach circumscribed the perspective of applied research, with a qualitative, survey-based, descriptive, bibliographic, and field approach. As a data prodution instrument, a survey was applied, semi-structured interviews were conducted with the educators participating in the study, and an institutional diagnosis survey of the school field was conducted. For data analysis, content analysis was anchored in Bardin's proposal (2011), focusing on the handling of the three fundamental phases in the analysis: pre-analysis, material exploration, and treatment of results - inference and interpretation. The study also referred to authors of musical education in early childhood education such as Bennett (1986),Beineke (2008), Bellochio (2001), Bréscia (2003), and Gainza (1988), among others. In the light of the research, the results made it possible to understand that the teachers still lack in-depth knowledge or training on the subject. As well as the need for musical resources or tools incorporated into teaching. Based on the data analyzed, an educational product entitled Pedagogical-musical dynamics applied to early childhood education, an orientation of pedagogical activities with Early Childhood Education educators working in the classroom with children, using music and developing cognitive, physical and social skills in early childhood.